ANALYSIS OF COLLECTION PRESERVATION IMPLEMENTATION IN SCHOOL LIBRARIES - Irmawati Irmawati; Nur Fadillah Rusli; Irvan Muliyadi; Saenal Abidin (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study, entitled "Analysis of Collection Preservation Implementation in School Libraries in two cities, Makassar and Kalimantan," aims to analyze the implementation of collection preservation in school libraries. This study uses a descriptive method with a qualitative approach that aims to describe various phenomena that occur in depth by emphasizing the characteristics, quality, and relationships between activities. Data sources in this study consist of primary data obtained directly from primary sources, as well as secondary data obtained through intermediaries. Data collection techniques used include observation, document review, and semi-structured interviews (in-depth interviews) using interview guidelines. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and verification or drawing conclusions. The results of the study indicate that preservation activities have been carried out in various forms, although still simple, such as book repairs, rebinding, providing covers, cleaning collections, and lamination in certain sections. In addition, some libraries have also implemented fumigation to prevent damage from mold and pests, although this is only done by a few schools. These conditions result in preservation activities not being carried out optimally and in a structured manner. Therefore, increased human resources, budget support, and adequate training are needed to ensure more effective and sustainable collection preservation activities.